Bajo las olas - Pratt-Serafini, Kristin Joy. (Nevada City, Calif. : DAWN Publications, 1995)
Uses the letters of the alphabet to introduce angelfish, dolphins, manatees, octopus, and other fish and mammals living in the world's oceans, giving their physical charactistics and behavior.
Accelerated Reader AR
Keywords: Fishes -- Juvenile literature; Environmental protection -- Juvenile literature; Marine animals -- Juvenile literature; Marine ecology -- Juvenile literature; Alphabet